. GAMBARAN MASALAH KESEHATAN PADA MASYARAKAT PASCA BANJIR LAHAR DINGIN GUNUNG MERAPI DI WILAYAH KERJA DI PUSKESMAS SRUMBUNG MAGELANG - Aditya, Fendy Jaya; Ambarwati, Winarsih Nur (Jurnal Berita Ilmu Keperawatan, 2010)
Post-eruption of Merapi was still had a problems for society that cold lava flood and cause a variety of impacts to the community both physically ie the onset of the disease in the community and the psychological impact of anxiety and depression among other communities. Srumbung Health Center as one of the government health agencies in areas affected by Merapi cold lava flood assisted services to people affected by Merapi cold lava flood. This study aims to describe the public health issues after Mount Merapi cold lava flood in the working area Srumbung Health Center. The study used a qualitative descriptive. The population of the district is all Srumbung. Sampling technique was total sampling. Collecting the documentation in the form of field notes. The data analysis using descriptive analysis. This study concluded that: (1) The number of patient visits in health centers is most Srumbung pharyngitis visits as many as 1313 or an average of 328.3 visits per month, and (2) The number of patient visits at the health center is the lowest Srumbung Gout average as much as 201 or visit 50.3 average visits per month. Keywords: cold lava flood, public health issues